Public (mis)understanding of the UV index - Carter, Owen; Donovan, Robert (Taylor and Francis Inc., 2007)
The ultraviolet index (UVI) has been regularly reported in Australia for a decadebut utilisation remains extremely low (5%). Blunden, Lower, and Slevin, in a2004 Journal of Health communication article, suggest that Australians' understandingof the UVI is "good," and education to increase awareness of the indexis therefore no longer warranted. To test this position, focus groups were conductedfollowed by an intercept survey of 404 residents of Perth, Western Australia, aged16-44 years, to explore understanding and familiarity with the UVI. Results suggestedthat far from being "good," the familiarity and understanding of the UVIof at least half of Australians is poor. This was exemplified by the following: meanestimations of average UVI values in summer and winter being highly exaggerated(19.8 and 11.8, respectively); 61.2% not appreciating that the UVI is independentof temperature; at least 55.0% not appreciating that UV conditions peak at solarnoon; and 23.3%of 22-44 year olds confusing the UVI with a "burn-time" measure.People who do not understand the UVI are unlikely to utilise it effectively. It thereforeremains possible that utilisation of the UVI remains low because understandingis poor. Future efforts to improve utilisation of the UVI, particularly among thoselooking at new display formats, may therefore be ineffective, unless they also incorporatestrategies to facilitate understanding of the measure.